Responsible tourism : concepts, theory and practice (CABI, 2012)
The primary intent for this book is to produce a broad, yet comprehensive, monograph on the concept of responsible tourism (RT), focusing on what is meant by the term and what it encompasses. The text thus presents a critical discourse on what RT is (chapters 2-4), its key tenets (chapters 5-8) and the extent to which they are applied and realized through illustrations and examples of responsibility (or otherwise) in tourism in practice (chapters 9-13).